Functional Polymorphisms in the Neuropeptide Y (NPY) Gene Associated with Egg Production in Thai Native, Black-Bone, and Commercial Laying Hens Using SNP Markers - Doungnapa Promket; Jennarong Kammongkun; Jiranan Insee; Wootichai Kenchaiwong; Khanitta Pengmeesri; Thassawan Somchan; Wuttigrai Boonkum (Animals)
This study aimed to identify single nucleotide polymorphism (SNP) loci within the coding sequence of the neuropeptide Y (NPY) gene and evaluate their association with egg production traits in Thai native chickens. The goal was to enhance productivity through selective breeding. A total of 117 chickens, including three Thai native breeds and commercial laying hens, were analyzed. The phenotypic traits measured included age at first egg production (AFEP), first egg weight (FEW), egg weight at 9 months (EW_9M) and 12 months (EW_12M) of egg production period, number of eggs at 9 months (NE_9M) and 12 months (NE_12M) of egg production period, number of eggs per month (EperM), and egg mass (EMs). The NPY gene was sequenced to examine the association between these traits and specific genotypes. The results showed that commercial laying hens (LC) significantly outperformed native breeds in overall egg production. Among the native breeds, Pradu Hang Dum (PH) demonstrated the earliest laying age and the highest cumulative egg production. Genetic diversity analysis revealed moderate heterozygosity levels (PIC = 0.22 to 0.50, He = 0.26 to 0.50). Specific SNP loci (SNP1, SNP2, SNP3, SNP4, SNP5, and SNP6) were found to be associated with key egg production traits, such as AFEP, FEW, EW_9M, EW_12M, NE_9M, NE_12M, EperM, and EMs. These findings highlight the potential of using genetic markers for improving egg production traits in Thai native chickens. By incorporating marker-assisted selection into breeding programs, this research supports the development of more efficient and sustainable poultry farming practices, particularly for local breeds. This study also underscores the importance of preserving genetic diversity while enhancing productivity, ensuring the long-term sustainability of native chicken populations.